The Path of Resilience: from the Individual Subject to the Political Subject - Granados-Ospina, S.J., Luis Fernando (Editorial Pontificia Universidad Javeriana, 2017)
This is a literature review that starts from some definitions of the category of resilience, identifying in them diverse tendencies and approaches. From an assessment of human experience and the significance of social interactions and community actions for the construction of resilience, the article allows us to explore the frontiers where resilience meets politics, understood in the broad sense as collective action. The resilient response would seek to configure personal and community senses and practices to face adversity, from a political action committed to human dignity. The method used is a literature review and a categorical analysis, which seeks to offer theoretical elements to put the resilience in dialogue with politics.